Simple Wet Chemical Route for Decoration of Multi-walled Carbon Nanotubes with Nickel Nanoparticles - Shrestha, Sabita; Bhatta, Jay Prashad (Journal of Institute of Science and Technology, 2020)
Due to high specific area and chemical stability, carbon nanotubes (CNTs) are considered to be an excellent support for metal nanoparticles. Carbon nanotube supported metal nanoparticles have applications in different fields. There are different techniques to attached metal nanoparticles on the surface of CNTs. This paper reports a simple wet chemical route to decorate the surface of oxidized multi-walled carbon nanotube (MWCNT) with nickel nanoparticles (NiNPs). The NiNPs decorated MWCNTs have different applications in different fields such as sensors, photocatalytic activity, hydrogen gas production, catalyst, to produce metallic nanowire etc. MWCNT was treated with nitric acid for purification and oxidation. Purification removes the impurities found in MWCNT and oxidation adds different oxygen functional groups. Raman spectroscopy shows the oxidation and attachment of nickel nanoparticles with the help of intensity, position and area ratio of D and G band. The introduction of an oxygen functional group on the surface of MWCNT after oxidation was studied by Infrared spectroscopy. Thermal analysis (thermogravimetric analysis; TGA and differential thermal analysis; DTA) revealed different thermal behavior of pristine, oxidized, and Ni decorated MWCNTs. TGA showed that the decomposition temperature decreased after oxidation and decoration with NiNPs. TGA also confirmed the purification of MWCNTs as well as the presence of nickel with the MWCNTs. Energy dispersive spectroscopy (EDS) also confirmed the presence of nickel in the sample.